The Relationship between Self-Concept and Learning Interest of AL Washliyah 3 Medan High School Students - Silvania, Dinda; Wulandari, Tria Halizah; Anisa, Sri; Nurmaida, Elma; Ramadhani, Ramadhani (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study was to analyze the relationship between self-concept and student’s learning interests. Self-concept is an individual’s perception of himself, which indudes cognitive, affective and behavioral aspects. Learning interest is the tendency of students to pay attention and be actively involved in the learning process. This study uses a quantitative approach with a correlational method. This population is all students of SMA AL Washliyah 3 Medan and the research sample consists of 25 grade XI students who were selected using a random technique. The results of the analysis showed that there was a fairly low relationship between self-concept and learning interest (r = 0,266). Thus, students with a positive self-concept tend to have a high interest in learning, while students with a negative self-concept tend to show low interest in learning.